2015
DOI: 10.1111/sbr.12129
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and implicit memory during sleep

Abstract: The purpose of this study was to indicate the changes in the implicit and explicit memory under awake and sleep conditions by using a battery that can measure different subsections of memory. 24 healthy individuals participated in this study. Modified versions of the Auditory Verbal Learning Test and the Modified Word Stem Completion Test were applied to the study and control groups within the scope of Modified Multiple Block Design (MMBD). While the control group did not listen to any words during sleep, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A variety of other studies have reported similar results (e.g., Deeprose & Andrade, 2006;Flouda et al, 2013;Quan et al, 2013). In addition, learning-related effects of perceptual priming appear to also be intact during sleep (Oniz et al, 2015). On the other hand, some studies have failed to find any learning-related priming effects during anesthesia (e.g., Bejjani et al, 2009).…”
Section: Perceptual Primingmentioning
confidence: 77%
“…A variety of other studies have reported similar results (e.g., Deeprose & Andrade, 2006;Flouda et al, 2013;Quan et al, 2013). In addition, learning-related effects of perceptual priming appear to also be intact during sleep (Oniz et al, 2015). On the other hand, some studies have failed to find any learning-related priming effects during anesthesia (e.g., Bejjani et al, 2009).…”
Section: Perceptual Primingmentioning
confidence: 77%
“…It has been shown that external stimuli applied during sleep have different effects, and even some cognitive processes occur during sleep [1][2][3]. In addition, it is known that cognitive processes such as memory are also positively affected by sleep and have an important role in consolidation [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%